An Interplay Between MRTF-A and the Histone Acetyltransferase TIP60 Mediates Hypoxia-Reoxygenation Induced iNOS Transcription in Macrophages - Yang, Yuyu; Yang, Guang; Yu, Liming; Lin, Lin; Liu, Li; Fang, Mingming; Xu, Yong (Frontiers in Cell and Developmental Biology, 2020)
Cardiac ischemia-reperfusion injury (IRI) represents a major pathophysiological event associated with permanent loss of heart function. Several inter-dependent processes contribute to cardiac IRI that include accumulation of reactive oxygen species (ROS), aberrant inflammatory response, and depletion of energy supply. Inducible nitric oxide synthase (iNOS) is a pro-inflammatory mediator and a major catalyst of ROS generation. In the present study we investigated the epigenetic mechanism whereby iNOS transcription is up-regulated in macrophages in the context of cardiac IRI. We report that germline deletion or systemic inhibition of myocardin-related transcription factor A (MRTF-A) in mice attenuated up-regulation of iNOS following cardiac IRI in the heart. In cultured macrophages, depletion or inhibition of MRTF-A suppressed iNOS induction by hypoxia-reoxygenation (HR). In contrast, MRTF-A over-expression potentiated activation of the iNOS promoter by HR. MRTF-A directly binds to the iNOS promoter in response to HR stimulation. MRTF-A binding to the iNOS promoter was synonymous with active histone modifications including trimethylated H3K4, acetylated H3K9, H3K27, and H4K16. Further analysis revealed that MRTF-A interacted with H4K16 acetyltransferase TIP60 to synergistically activate iNOS transcription. TIP60 depletion or inhibition achieved equivalent effects as MRTF-A depletion/inhibition in terms of iNOS repression. Of interest, TIP60 appeared to form a crosstalk with the H3K4 trimethyltransferase complex to promote iNOS trans-activation. In conclusion, we data suggest that the MRTF-A-TIP60 axis may play a critical role in iNOS transcription in macrophages and as such be considered as a potential target for the intervention of cardiac IRI.